Wacana tradisi pela dalam masyarakat Ambon - Thomas, Frans (citeus, 2010)
The study is aimed to describe pela tradition discourse in Ambonese so-ciety. Qualitative Study with hermeneutical design is applied in this study. The data from oral discourse can be used as the primary data that focus on analysis, and other data in translating the meaning of oral discourse. Hermeneutical model is used in analyzing the data. The four aspects of the study were comprehended carefully through the semantic, reflective and existential levels. The findings of the study have both theoretical and practical implications. Theoretically, it has implication on the culture study, discourse analysis, oral action and sociolinguistics. Practically, it is valuable in determining policy in maintaining ethnic culture and enrichment the ref- erences in planning soft skill and local content instruction in schools.